Investigação diagnóstica de erros inatos do metabolismo em um hospital universitário - Amâncio, Fátima Aparecida Mazzini [UNESP] (2007)
Objective: To establish the frequency of inborn errors of metabolism (IEM) in a cohort of patients with a diagnostic hypothesis of IEM, deriving from the Hospital das Clínicas da Faculdade de Medicina de Botucatu of UNESP and to analyse the methodology used for this investigation. Methods: 1,233 urine samples from 905 patients were screened for IEM by chemical tests and chromatographic techniques. Results: IEM were diagnosed in 18 patients; twelve of these showed alterations in the IEM screening procedures (chemical tests and chromatography). All the 18 patients were diagnosed by enzymatic analyses. Conclusion: The IEM frequency diagnosed in this study (1.98%) was reasonable, since this group of patients came from a single hospital. The methodology proved to be efficient, indicating 12 IEM cases among the 18 diagnosed. The study shows the importance of specialized laboratories for the detection of this kind of pathology.